Lucknow Boy : A Memoir - Mehta, Vinod 1941- (New Delhi Penguin Books, 2011)
Autobiography of Vinod Mehta, born 1941, Indian editor and journalist.
Include Index
Keywords: India -- Journalists -- Periodical editors